Study Of Laser Scanning Data Redundancy For Constructing Digital Simulation Of Terrain - Kochneva Alina A, Vinogradov Evgenii A; Sankovsky Alexander A (International Journal of Advanced Science and Technology, 2020)
The article describes the method of constructing digital simulation of terrain, based on data of aerial laser scanning. Algorithm of interpolation of data obtained by means of terrain laser scanning, is described here, it enables to efficiently perform thinning laser reflection points which are insignificant for describing terrain. Data redundancy is identified via calculating the distance from the point to the plane, including three neighboring points for it in various directions. The universality of this algorithm should be noted, the algorithm fits for various areas of activity, including digital simulations of mines, mine workings. The suggested way of identifying data redundancy is implemented by means of simple mathematical operations, through that, lower computational complexity of the algorithm is obtained, compared to proprietary analogs, which enables to increase the capacity of thinning large arrays of laser reflection points